NOP2/Sun RNA Methyltransferase 4 Regulates the Mammalian Target of Rapamycin Signaling Pathway to Promote Hepatocellular Carcinoma Progression - Wang, Congren; Ke, Shaoying; Lin, Shaoze; Lin, Conglin; Cai, Zhibing; Hong, Lingju; Pan, Qunxiong (Turkish Journal of Gastroenterology, 2025)
Background/Aims: NOP2/Sun RNA methyltransferase 4 (NSUN4) is a prognostic indicator for hepatocellular carcinoma (HCC). However, the mechanism of NSUN4 in HCC is still unexplored. This project mainly focuses on the function and mechanism of NSUN4 in HCC malignant progression. Materials and Methods: The relation between the expression level of NSUN4 and the prognosis of HCC was measured by the means of bioinformatics. The expression level of NSUN4 was assessed by quantitative reverse transcription polymerase chain reaction. The western blot was utilized to determine the protein expression level of NSUN4 and mammalian target of rapamycin (mTOR) pathway-related proteins in cells and mouse tumor tissues. Cell counting kit-8 and colony formation assays were employed to measure cell proliferation ability. The wound healing assay and Transwell experiment were conducted to measure the cells’ migration and invasion abilities. Flow cytometry was applied to determine the cell cycle. Results: NSUN4 was overexpressed in HCC tissues and cells, enhancing cell migration, proliferation, and invasion. The influence that NSUN4 exerted on HCC malignant progression could be reduced by the inhibitor of the mTOR pathway. Conclusion: The study explained the mechanism and influence of NSUN4 on HCC progression by regulating the mTOR signaling pathway through in vitro and in vivo experiments, providing the theoretical basis and a new research direction for clinical prognostic prediction and treatment. Cite this article as: Wang C, Ke S, Lin S, et al. NSUN4 regulates the mTOR signaling pathway to promote HCC progression. Turk J Gastroenterol. 2025;36(1):24-33.